Wie beunruhigend ist das steigende Alter von Vätern bei der Geburt eines Kindes? : Eine historische Einordnung - Willführ, Kai Pierre; Klüsener, Sebastian (Gynakologische Endokrinologie, 2025)
In recent decades the average paternal age at childbirth has risen sharply. Many researchers from various disciplines are alarmed, as the offspring of older fathers have a higher risk of many diseases; however, previous studies lack a historical perspective. A new analysis shows that in many countries the current levels of average paternal age at childbirth were just as high in the past as today.
Keywords: Historical development; Individual level outcomes; LPAC database; Offspring health; Paternal age effect; Population level outcomes